Green design creative, sustainable designs for the twenty-first century - Fairs, Marcus (Carlton, 2009)
Shows how the design world is responding to the environmental challenges of the twenty-first century. This book considers the parallel issue of social sustainability, where the welfare of factory workers is given equal importance to environmental issues.